2018
DOI: 10.1038/s41598-017-18759-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase (GST) of American Cockroach, Periplaneta americana: Classes, Isoforms, and Allergenicity

Abstract: Insect glutathione S-transferases (GSTs) play important roles in insecticide/drug resistance and stress response. Medically, GSTs of house dust mites (Dermatophagoides pteronyssinus and Blomia tropicalis) and German cockroach (Blattella germanica) are human allergens. In this study, classes, isoforms and B-cell and allergenic epitopes of GST of American cockroach, Periplaneta americana, the predominant species in the tropics and subtropics were investigated for the first time. Enzymatically active native and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…GSTs also offer additional protection against the effects of insecticides by reducing oxidative stress (Silva et al., ; Vontas, Graham, & Hemingway, ). It is also important to note that GSTs from the German cockroach (Bla g 5) and the American cockroach as well as from other arthropods and nematodes, are clinically relevant human allergens (Arruda et al., ; Sookrung et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…GSTs also offer additional protection against the effects of insecticides by reducing oxidative stress (Silva et al., ; Vontas, Graham, & Hemingway, ). It is also important to note that GSTs from the German cockroach (Bla g 5) and the American cockroach as well as from other arthropods and nematodes, are clinically relevant human allergens (Arruda et al., ; Sookrung et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional GSTs from German cockroach have been identified, though these have not been submitted to the WHO/IUIS committee with proof of IgE binding: another sigma GST (EF202178), a theta GST (AEV23882) and two delta GSTs (ABX57814 and AEV23880). Two GSTs from the American cockroach ( Periplaneta americana ) were identified as binding IgE, and they belong to the delta class of GSTs [MG255130 (13) and AEV23867] and share 99.54% amino acid identity. When these GSTs were submitted, we decided to include them as Per a group 5 proteins even though their identity to Bla g 5 was only 19% identity with Bla g 5.…”
Section: Challenges For Future Allergen Namesmentioning
confidence: 99%
“…Unfortunately, since allergic conditions were not excluded when the serum samples were collected and because the medical history of allergic diseases from our negative control population was unknown to us, it is only possible to make this a speculative, and not a final conclusion. However, based on previous studies, the frequency of allergies in this negative population could very well be high (CDC, 2004; Perez-Perdomo et al, 2003), especially since GST is one of the many organisms that have been commonly reported as human allergens (Acevedo et al, 2013; Sookrung et al, 2018). The cross-reactivity of GST between different mite species (Huang et al, 2006; Liao et al, 2013) and fungal sources (Huang et al, 2006; Liao et al, 2013), as well as the cross-reactivity of GST between mites and cockroaches (Huang et al, 2006; Liao et al, 2013) and recently even between cockroaches and helminthes has been demonstrated (Santiago et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…We have speculated that the reactivity of GST with some negative sera “in absence of parasitic infection” could be due to cross-reactions with antibodies elicited by GST derived from allergenic organisms such as mites, cockroaches, or pollen, which have been implicated as responsible agents for asthma in the US and other countries (Deifl et al, 2014; Mueller et al, 2015; Sookrung et al, 2018). Unfortunately, since allergic conditions were not excluded when the serum samples were collected and because the medical history of allergic diseases from our negative control population was unknown to us, it is only possible to make this a speculative, and not a final conclusion.…”
Section: Discussionmentioning
confidence: 99%